Exploring selected Traditional and Contemporary Repertoires of Malay Gamelan on the Keromong - Amira Farhana Binti Ahmad Hamidi; Huey Yi Wong (Universitas Negeri Medan, 2025)
This study examines the performance techniques of the keromong, a key melodic instrument in the Malay gamelan ensemble, focusing on both traditional and modern repertoires. Despite its central role, systematic documentation of keromong techniques remains limited, mainly because traditional teaching methods are mostly transmitted orally. Guided by constructivist learning theory, this research uses a qualitative approach, combining performance observation, semi-structured interviews, audiovisual analysis, and reflective journaling. The study explores three core techniques introduced by the late Adiguru Bob Khalil - Irama Satu (Simultaneous Rhythm), Irama Dua (Alternating Rhythm), and Irama Bertingkah (Interlocking Rhythm) and demonstrates how they are applied in both classical pieces (Timang Burung) and new compositions (Overture Maharajawana, Maharajawana, and Nafas). These techniques, integrated with the researcher’s interpretive choices, such as dynamic playing/ hitting, expressive hand gestures, and controlled breathing, enhance the emotional and visual aspects of performance. The findings show that traditional techniques, while rooted in heritage, can be effectively adapted for contemporary compositions, enriching musical interpretation and expression. This study contributes to the ongoing discussion of Malay Gamelan pedagogy by proposing a structured, accessible teaching model that complements oral traditions and provides visual or written guidance for learners. It highlights the potential of performance-based research to preserve cultural heritage while fostering innovation.